A Statistical analysis on Pangilinan Electronics Enterprises - Lavin, Caitlin Mae; Penalosa, William Albert; Ponferrada, Regidor (Diliman, Quezon City College of Engineering, 2001)
This is a study conducted on Pangilinan Electronics Enterprises. Pangilinan Electronics Enterprises is a professional manufacturer of electrical transformers, Regulated Power Supply for communication equipment, Guitar Amplifiers, AC to DC adaptors, electronic modules and AVRs (Automatic Voltage Regulators). The study focuses on the AVR-500 is a commercially available AVR with an input voltage of 200 volts and output voltage of 220+5 percent and 110+5 percent volts. The study identified that the main problem with the AVRs being produced is the high percentage of defective units produced. The group conducted problem analysis and verification to determine the most probable causes of AVR defectives. This was done through interviews and plant visits. The group was able to point out three main factors that lead to AVR defects. The factors are capacitor defect, relay defect and the worker. The first test done by the group was the test of proportion. This test was done to test the company's claim that the rejection rate for the first production run is 15 percent. The test verified the company's claim that the rate of rejection during the first production run is 15 percent. The group then conducted Runs Test of Randomness to see if the data acquired was randomly distributed. The test verified that the sample was randomly taken. After testing the randomness of the data the group conducted a One sample Sign test to see if the sample means are equal. The test concluded that the sample mean and the hypothesized means are unequal. The next test used was the test of hypothesis on the ratio of two variances. The variances compared were compared from the values above the accepted range and the values below the accepted range. The test determined that the variances are unequal with the variance of the values above the acceptable range being larger than that of the values below the acceptable range. The implication of this is that the values above the acceptable range are more dispersed as compared to the values below the acceptable range. The X2 Goodness of fit test on the proportions/percentage of defects was then done to test the claim of the company that rejection rate follows a uniform distribution with the first week having twice as many defects as any other week. This test verified the claim that the distribution is uniform with the number of rejects in the first production run being twice as many as the succeeding production runs.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 28 : Statistical Analysis for Industrial Engineering
Keywords: Statistics